2010
DOI: 10.3103/s0095452710030011
|View full text |Cite
|
Sign up to set email alerts
|

Allelic polymorphism of F2, F5 and MTHFR genes in population of Ukraine

Abstract: Analysis of F2, F5 and MTHFR genes SNPs allelic vari ants in population of G20210A SNP, GG (96.5 %), GA (3.5 %) for F5 gene G1691A SNP and CC (49.5 %), CT (43 %), TT (7.5 %)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…The incidence of heterozygotes in the general population is about 45%, with geographical and ethnic variations (5). The prevalence in Southeastern Europe countries are 45%, 43%, 40%, in Hungary, Ukraine, Russia, respectively (5,26). Although a study performed in Germany showed a 2.12 increased risk of DVT for individuals with the heterozygous genotype, found in 43.8% of patients, the majority of studies showed no association with VTE, concordant with our results (33,(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of heterozygotes in the general population is about 45%, with geographical and ethnic variations (5). The prevalence in Southeastern Europe countries are 45%, 43%, 40%, in Hungary, Ukraine, Russia, respectively (5,26). Although a study performed in Germany showed a 2.12 increased risk of DVT for individuals with the heterozygous genotype, found in 43.8% of patients, the majority of studies showed no association with VTE, concordant with our results (33,(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…26 (24,29,33,35,36) and a 20% increased risk of VTE (37), whereas other studies failed to reveal any significant association (25,(38)(39)(40). Previous Romanian studies regarding thrombophilia in obstetric cases detected frequencies of the homozygous MTHFR 677TT genotype of 19.4% and 19.56% in pregnant patients with haemorrhagic complications and in patients with repetitive spontaneous abortions; no significant associations were found, except for a slightly increased risk for repetitive abortions in the presence of this genotype (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But for MTR A2756G and MTRR A66G polymorphisms, there are not enough studies. Hence, further studies are need to be conducted (Table 1) [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. …”
Section: Genetic Susceptibility and The Risk Of Msmentioning
confidence: 99%